The role of social media in collective learning / Khalid Abdul Wahid , Wan Saiful 'Azzam Wan Ismail dan Haruthai Numprasertchai - Abdul Wahid, Khalid; Wan Ismail, Wan Saiful 'Azzam; Haruthai, Numprasertchai (Inderscience Publishers, 2019)
In the first decade of the 21st century, e-learning has become one of the key factors in the revolution of learning process. E-learning combines modern interactive learning methods with knowledge management methods that provide better evaluation of knowledge. Social media, as one of ICT tools, has brought revolutionary new ways of interacting, participating, cooperating and collaborating which involve users generating content and connecting with people through a 'many-to-many', rather than the traditional 'one-to-many', communication approach. However, collective learning using social media among higher institution students has not been given much attention especially within a Malaysian context. Therefore, the main purpose of this study is to investigate the acceptance of social media in learning among higher institution students. Data from 359 students were collected from both science and technology and social science clusters at Universiti Teknologi MARA (UiTM). Data was analysed using SmartPLS. The result showed that all antecedents of technology acceptance which included performance expectancy, effort expectancy and facilitating condition have positive significant effect on collective learning except social influence.